Chromatin Diminution and C-value Enigma - Grishanin, Andrey (Contemporary Research and Perspectives in Biological Science Vol. 3, 2024)
This work considers non-genic DNA as an element of the genome that allows regulating the frequency of recombination processes during evolution, which allows a species to find the optimal genotype variant corresponding to environmental conditions. From this point of view, chromatin diminution is a special case of genome size change, during which the genome of somatic line cells in multicellular organisms or the somatic nucleus in Protozoa is reduced. A model of the origin of chromatin diminution in cyclops and the role of chromatin diminution in speciation are considered.